2019
DOI: 10.1093/heapro/daz111
|View full text |Cite
|
Sign up to set email alerts
|

Why staff at European schools abstain from enforcing smoke-free policies on persistent violators

Abstract: Summary Secondary schools in European countries increasingly implement comprehensive smoke-free school policies (SFSPs) that prohibit most or even all adolescents from smoking during school hours. Consistent enforcement of SFSPs is essential for realizing optimum effectiveness. A main challenge represents adolescents who persistently violate the rules. We studied how staff in European countries respond to these persistent violators and why they may turn a blind eye. We used interview transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…In many secondary schools, STPs are not well implemented [ 22 25 ]. A systematic review found that key contextual factors for successfully implementing tobacco- and substance-use interventions in secondary schools are a positive organizational climate, adequate training, and teachers’ and students’ motivation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many secondary schools, STPs are not well implemented [ 22 25 ]. A systematic review found that key contextual factors for successfully implementing tobacco- and substance-use interventions in secondary schools are a positive organizational climate, adequate training, and teachers’ and students’ motivation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Moreover, the discourses can be said to echo a broader health-political debate concerning which means and models are most appropriate for health promotion and tobacco control. 44,45 As with other research on STPs 22,24,26 , we identi ed staff and managerial perceptions that students' smoking behavior is a less important issue to address than other health behaviors, such as students' well-being, as a barrier to change commitment. Moreover, in line with other research 17,19,40 our study shows that enforcement is seen as a practice that might negatively affect teacher-student relations.…”
Section: Discussionmentioning
confidence: 99%
“…In many secondary schools, STPs are not well implemented. [21][22][23][24] A systematic review found that key contextual factors for successfully implementing tobacco-and substance-use interventions in secondary schools are: a positive organizational climate, adequate training and teachers' and students' motivation. 25 Barriers to implementation include heavy workloads, budget cuts and lack of resources or support.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Möglichkeit zur Erhöhung der Effektivität der Durchsetzung des Rauchverbots würde in der Einbindung schulexterner Fachkräfte bestehen, da das interne Schulpersonal aufgrund begrenzter Zeitressourcen und anderer Prioritäten im Schulalltag dies schlichtweg nicht allumfänglich zu leisten vermag [32]. Qualitative Studien verweisen darauf, dass Lehrer*innen aus Gründen der Skepsis gegenüber der Effektivität von sanktionierenden Tabakkontrollmaßnahmen und eines priorisierenden Fokus auf die Persönlichkeitsentwicklung der Jugendlichen eher davon absehen, die schulische Tabakkontrolle strikt umzusetzen [33,45] [7,8,16]. Jüngere Trenddaten für Deutschland zeigen zudem eine Persistenz von SES-Unterschieden in der häuslichen Passivrauchbelastung auf [13,18].Diesbetrifftebenso andere private Kontexte wie die toxische Tabakexposition im Automobil [36].…”
Section: Discussionunclassified